2004
DOI: 10.1261/rna.7930804
|View full text |Cite
|
Sign up to set email alerts
|

Photolabile anticodon stem–loop analogs of tRNAPhe as probes of ribosomal structure and structural fluctuation at the decoding center

Abstract: With the recent availability of high-resolution structures of bacterial ribosomes, studies of ribosome-catalyzed protein biosynthesis are now focusing on the nature of conformational changes that occur as the ribosome exerts its complex catalytic function. Photocrosslinking can be relevant for this purpose by providing clues to ribosomal structural fluctuations and dynamics. Here we describe crosslinking experiments on 70S ribosomes using two photolabile anticodon stem-loop derivatives of Escherichia coli tRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Site-directed cross-linking studies with 4-thiouridine identified a cross-link between residue U14 of helix 1 and the 903-904 region of helix 27, very close to the 900 tetraloop (Juzumiene and Wollenzien 2001), but such a cross-link is incompatible with the crystal structure of the 30S subunit. It is known that the top of helix 44 and neighboring helices, such as helices 1 and 27, have some conformational flexibility (VanLoock et al 2000;Gabashvili et al 2003;Druzina and Cooperman 2004), but a direct contact between nucleotides U14 and 902-903 would require the disruption of helix 2 and a drastic displacement of helices 1 and 27. Rather, we propose that mutations in helix 1 affect the 900 tetraloop indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…Site-directed cross-linking studies with 4-thiouridine identified a cross-link between residue U14 of helix 1 and the 903-904 region of helix 27, very close to the 900 tetraloop (Juzumiene and Wollenzien 2001), but such a cross-link is incompatible with the crystal structure of the 30S subunit. It is known that the top of helix 44 and neighboring helices, such as helices 1 and 27, have some conformational flexibility (VanLoock et al 2000;Gabashvili et al 2003;Druzina and Cooperman 2004), but a direct contact between nucleotides U14 and 902-903 would require the disruption of helix 2 and a drastic displacement of helices 1 and 27. Rather, we propose that mutations in helix 1 affect the 900 tetraloop indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…Except as specified below, materials were obtained and methods were performed as described elsewhere ( ). 5-Iodoacetamido-fluorescein (IAF), 7-diethylamino-3-((((2-maleimidyl)ethyl)amino)carbonyl)coumarin (MDCC), and 7-diethylamino-3-(4‘-maleimidylphenyl)-4-methylcoumarin (CPM) were obtained from Molecular Probes.…”
Section: Methodsmentioning
confidence: 99%
“…Specific reaction conditions will be based on our studies with RNase P RNA; however, such conditions are similar to that in other in vitro studies of RNA biochemistry. Indeed, some or all of the methods described in this chapter have been successfully applied in analysis of structural and catalytic RNAs as well as the major cellular RNPs, including the ribosome, and the spliceosome (Christian et al , 1998; Druzina and Cooperman, 2004; Harris et al , 1994, 1997; Huggins et al , 2005; Juzumiene and Wollenzien, 2001; Juzumiene et al , 2001; Kim and Abelson, 1996; Leung and Koslowsky, 1999; Maroney et al , 1996; Montpetit et al , 1998; Newman et al , 1995; Pinard et al , 1999; Pisarev et al , 2008; Podar et al , 1998; Rinke-Appel et al , 2002; Ryan et al , 2004; Sergiev et al , 1997; Wassarman and Steitz, 1992; Yu and Steitz, 1997). Crosslinking is thus likely to remain a very useful tool in deconstructing the structure and function of RNAs and RNPs for many years to come.…”
Section: Introductionmentioning
confidence: 99%